JURNAL PENGARUH DISIPLIN KERJA, KOMITMEN, DAN KARAKTERINSTIK INDIVDU TERHADAP TOTAL QUALITY MANAGEMENT PT SAHABAT UNGGUL INTERNATIONAL - Sendi Cahyani; Pitaloka Dharma Ayu; Sri Rahayu (BISECER (Business Economic Entrepreneurship), 2023)
Total Quality Management is often used as an indicator that determines the success or failure of a company within a certain period of time. The achievement of Total Quality Management at PT Sahabat Unggul International for the last seven years has not been maximized, and even tends to decrease. Factors that can affect total quality management include work discipline, commitment and individual characteristics. The purpose of this study was to determine the effect of work discipline, commitment, and individual characteristics on the total quality management of PT Sahabat Unggul International. PT Sahabat Superior International has high employee delays, 46% of employees go in and out per year, and the knowledge and skills of employees are not maximized, so the total quality management at PT Sahabat Superior International is still low.The type of research used is explanatory research, so this research is associative research which aims to determine the relationship between two or more variables (Sugiyono, 2018). The variables used in this study are work discipline, commitment and individual characteristics as independent variables and total quality management as the dependent variable. The population is 800 employees with a tolerance limit of 10% according to the sample calculation in this study totaling 200 employees of PT Sahabat Unggul International. This study uses the Non Probability Sampling method (not the entire population is taken).Work discipline, commitment, and individual characteristics together affect the total quality management of PT Sahabat Unggul International employees with a correlation coefficient value of 0.735 for work discipline, 0.760 for commitment and 0.741 for individual characteristics, which if interpreted, the trend is included in strong category. Work discipline, commitment, and individual characteristics also have a positive influence on total quality management as indicated by the regression coefficient value of work discipline 0.679, commitment of 0.701, and individual characteristics of 0.657 meaning that work discipline, commitment, and individual characteristics have a positive effect on total quality management.The t-test coefficient for work discipline is 4.166, commitment is 3.697 and the individual characteristic regression coefficient is 2.899. The influence of work discipline, commitment and individual characteristics together affects the total quality management at PT Sahabat Unggul International which is shown from the results of the determination test of 63% with a calculated F value of 113.33 which is greater than F table 2.65 and significance of 0.000 which is smaller than the 0.05 level of significance.